Virtual reality cognitive-behavioral therapy biofeedback system for glossophobia - Correia, António (2023)
The fear of public speaking is one of the most common social phobias causing anxiety problems in many people. In this context, this project focuses on developing a tool capable of helping mental health professionals using virtual reality as a controlled environment in expository therapies, in this case applied to Glossophobia. To enhance the creation of self-control mechanisms in these patients, the use of virtual reality is explored with the aid of Neuro and Biofeedback, allowing the visualization in real time of the physiological response to the stimuli of the virtual environment.